Community pharmacists’ willingness and barriers to provide vaccination during COVID-19 pandemic in Jordan - Anan S. Jarab; Walid Al-Qerem; Tareq L. Mukattash (Human Vaccines & Immunotherapeutics, 2022)
Providing vaccination in community pharmacies could increase the vaccination coverage rate as well as help reducing the workload of the healthcare system. The current study was conducted to evaluate community pharmacists’ willingness and barriers to provide vaccination in community pharmacy setting. A validated questionnaire which included eight items to evaluate willingness and eleven items to evaluate the barriers to provide vaccines was distributed online. Binary logistic regression was conducted to explore the factors that are significantly associated with willingness and barriers to provide the vaccine. Among the 201 participating pharmacists, 174 (86.6%) had a high willingness level. Lack of authorization (91.6%), lack of collaboration with other healthcare professionals (85.6%), and lack of space for storage (74.1%) were the most recognized barriers to vaccinate. Pharmacists with BSc degree demonstrated less willingness (OR = 0.18 (0.07–0.46), and increased barriers (OR = 4.86 (1.56–15.17) to provide the vaccine when compared with Pharm D and postgraduate pharmacists P < .01. Factors including male gender (OR: 6.10), working in chain pharmacy (OR: 8.98) and rural areas (OR: 4.31), moderate income (OR: 19.34) and less years of experience (OR:0.85) were significantly associated with increased barriers to provide the vaccine (P < .05). Despite the high willingness of the community pharmacists to vaccinate, several barriers were present. Enhancing pharmacists’ authorization and collaboration with other healthcare professionals and providing space for storage along with providing training courses and workshops should be considered to enhance pharmacist’s engagement in vaccination service.